2014
DOI: 10.1097/mnh.0000000000000071
|View full text |Cite
|
Sign up to set email alerts
|

Current status of kidney transplantation in HIV-infected patients

Abstract: Renal transplantation remains the optimal treatment for end stage renal disease in the HIV-infected patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Currently, 2 main approaches have been proposed to address this issue. First, dose finding and pharmacokinetics studies have been conducted with promising results in predicting post-transplant TAC levels (31,32), and second, it is suggested that HIV-infected patients have their ARV regimen changed before transplantation, switching candidates to an integrase-based regimen (33). As previously reported, the incidence of DGF after deceased-donor kidney transplantation is very high in Brazilian transplant centers, and this was also observed in this study (13,14).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Currently, 2 main approaches have been proposed to address this issue. First, dose finding and pharmacokinetics studies have been conducted with promising results in predicting post-transplant TAC levels (31,32), and second, it is suggested that HIV-infected patients have their ARV regimen changed before transplantation, switching candidates to an integrase-based regimen (33). As previously reported, the incidence of DGF after deceased-donor kidney transplantation is very high in Brazilian transplant centers, and this was also observed in this study (13,14).…”
Section: Discussionsupporting
confidence: 73%
“…Currently, 2 main approaches have been proposed to address this issue. First, dose finding and pharmacokinetics studies have been conducted with promising results in predicting post‐transplant TAC levels , and second, it is suggested that HIV‐infected patients have their ARV regimen changed before transplantation, switching candidates to an integrase‐based regimen .…”
Section: Discussionmentioning
confidence: 99%
“…This epidemiological shift translates into a continuous rise in non-AIDSrelated ICU admissions which broadly exceeded those for severe OIs in most of recent cohorts. Furthermore, on the basis of encouraging outcomes, HIV infection is no longer a definite contra-indication for SOT in patients with chronic kidney, liver or heart failure, thereby enlarging the scope of critical illnesses in this population [25][26][27].…”
Section: The Current Landscape Of Hiv Infection In the Icumentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19] At the time of this finding, this poor renal outcome was possibly, in part, due to a higher rate of acute rejection of PLHIV because of insufficient induction therapy. 8,20 However, although KT should be the standard of care for eligible PLHIV, 18,21 nephrologists might still be reluctant to offer this therapeutic option, for fear of a higher risk of general or surgical site infection 9,22,23 due to profound immunosuppression. 8,20 However, although KT should be the standard of care for eligible PLHIV, 18,21 nephrologists might still be reluctant to offer this therapeutic option, for fear of a higher risk of general or surgical site infection 9,22,23 due to profound immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Indeed, the importance of T cell depleting induction in PLHIV has only recently been established. 8,20 However, although KT should be the standard of care for eligible PLHIV, 18,21 nephrologists might still be reluctant to offer this therapeutic option, for fear of a higher risk of general or surgical site infection 9,22,23 due to profound immunosuppression. The possible interactions between antiretroviral and immunosuppressive drugs requiring complex drug monitoring 24,25 might also be a disincentive.…”
Section: Introductionmentioning
confidence: 99%